Curriculum Development Strategies in Five Countries: A Literature Review - Marhamah Marhamah; Annisa Zahra Putri; Dian Andriyani; Hanifah Rahma; Nabila Syafira (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to investigate curriculum development strategies in five countries—Finland, Indonesia, the United States, Japan, and Singapore—through a qualitative library research approach. Curriculum reform has become a global priority in response to rapid technological advancement, globalization, and changing educational demands. This study reviews 50 scholarly sources, consisting of 10 references for each country, including journal articles, policy documents, and official government reports. The analysis focuses on key aspects of curriculum development, namely governance structure, curriculum orientation, teacher autonomy, assessment practices, and technology integration. The findings indicate that while all five countries emphasize competency-based learning and the integration of technology to improve learning quality, they differ significantly in curriculum governance, flexibility, and implementation strategies. Finland and the United States demonstrate higher levels of decentralization and teacher autonomy, whereas Indonesia, Japan, and Singapore apply more centralized curriculum systems. Common challenges identified include ensuring educational equity, enhancing teacher readiness, and adapting curricula to rapid societal and technological changes. This study contributes to a comparative understanding of international curriculum strategies and provides insights for improving curriculum design through evidence-based and technology-supported approaches.